The Jew, the Arab: a history of the enemy - Anidjar, Gil (Cultural memory in the present, 2003)
The theological enemy -- Derrida, the Jew, the Arab -- De inimicitia -- Rosenzweig's war -- The enemy's two bodies (political theology, too) -- Muslims (Hegel, Freud, Auschwitz) -- Corpse of law : the Messiah and the Muslim